2004
DOI: 10.1364/opex.12.006088
|View full text |Cite
|
Sign up to set email alerts
|

Ytterbium-doped large-core fiber laser with 1.36 kW continuous-wave output power

Abstract: We have demonstrated a highly-efficient cladding-pumped ytterbium-doped fiber laser generating 1.36 kW of continuous-wave output power at 1.1 mum with 83% slope efficiency and near diffraction-limited beam quality. The laser was end-pumped through both fiber ends and showed no evidence of roll-over even at the highest output power, which was limited only by available pump power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
340
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 836 publications
(352 citation statements)
references
References 8 publications
(12 reference statements)
4
340
0
8
Order By: Relevance
“…As in our system, with a V value of 3.53, the fiber can only support four modes at most. By coiling the fiber onto a 20 cm-diameter aluminum spool, higher modes in the fiber are suppressed [21]. With two multimode FBGs, the lasing modes in the multimode fiber get double selected.…”
Section: Resultsmentioning
confidence: 99%
“…As in our system, with a V value of 3.53, the fiber can only support four modes at most. By coiling the fiber onto a 20 cm-diameter aluminum spool, higher modes in the fiber are suppressed [21]. With two multimode FBGs, the lasing modes in the multimode fiber get double selected.…”
Section: Resultsmentioning
confidence: 99%
“…Focused development under the DARPA SHEDs program has also lead to extremely high power conversion efficiency in the 9xx-nm wavelength band, leading to diode bars with efficiency in excess of 74% and a clear route to efficiencies superior to 85% at room temperature (Crump et al, 2007). With demonstrated slope efficiency of optical fibers on the order of 80% (Jeong et al, 2004) and a demonstrated efficiency of spectral beam combining techniques of 91% (Drachenberg et al, 2011), we consider in this paper a global E/O efficiency of 50%. Detailed calculations performed on Forsterite by Thiry et al (2016) indicate that the coupling coefficient of a CW laser operating under the plasma formation intensity near the 1 micron wavelength is dictated mainly by 2 parameters: the laser intensity Φ [W/m 2 ] which depends on the laser output power and focusing ability of the optics as well as the mean time available to heat the material which is roughly proportional to the ratio between the laser beam diameter and the relative speed of the asteroid surface with respect to the laser beam (on the order of 6 cm/s if one considers the spin-limit of a 156 m asteroid).…”
Section: Laser Ablationmentioning
confidence: 99%
“…In the last decade, output power of fiber lasers increase dramatically. In the laboratory, several kilowatts can be achieved with a single fiber [1] and mature products of kW fiber laser can be offered in the field of industry [2].…”
Section: Introductionmentioning
confidence: 99%